Analysis of Total Alkaloid from Ethanol Extract of Butterfly Pea Flower Leaves (Clitoria Ternatea L.) Using UV-VIS Spectrophotometry Metodh - Herlina Herlina; Elly Mulyani; Betna Dewi; Bunga Diah Ayu Pratiwi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Clitoria ternatea L. Is a medicinal plant known to contain various secondary metabolites including flavonoids, tannins, terpenoind, saponins, steroids and alkaloids. Alkaloids exhibit various therapeutic activities, including antimalarial and anticancer effects. This study aimed to determine the total alkaloid content of ethanolic extract of Clitoria ternates L.. leaves. The extract was prepared by the maceration metodh using 96% ethanol as the extraction solvent. The presence of alkaloids in the extract was qualitatively identified using mayer, dragendoff and wagner reagents, while the total alkaloids content was quantitatively determined by the UV-Visible spectrophotometric metodh using caffeine as the standard solution. The result s showed that the ethanolic extract of Clitoria ternatea L. Leaves tested positive for alkaloids, with a total alkaloid content of 0,928%.